Science, Technology, and Society : New Directions - Webster, Andrew, 1951- (Book collections on Project MUSE., 1991)
"Read any newspaper or watch your television and as often as not you will be confronted by the worries, hopes, challenges, and mistakes of science and technology. Sociology has been trying to make sense of science for many years, while government and industry have promoted and exploited it for even longer. But what are science and technology? How have they been shaped by society? What new directions are they taking?"--BOOK JACKET. "Andrew Webster provides a lively and accessible introduction to the sociological analysis of science and technology, exploring contemporary debates in a comprehensive and balanced fashion and showing how the findings of sociologists of science relate to important issues of science policy and politics."--BOOK JACKET. "Biotechnology and genetic engineering, technology transfer, feminist and radical critiques of science, "big science" projects, science parks and research within private industry are some of the topics that provide the focus for a wide-ranging, critical yet constructive sociological discussion. Science, Technology, and Society will be of particular value to students, academics, and practitioners involved in studying and helping to shape these two very powerful institutions of society."--Jacket.